Connecting the Dots: Transcriptomic Approaches and Relationship between Myocardial Infarction and Breast Cancer - Miftahul Khair Akbar; Fadilah Fadilah; Arief Aulia Rahman (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Myocardial infarction, resulting from coronary blood vessel blockage, inflicts lasting damage on the heart muscle. Meanwhile, breast cancer ranks among the most diagnosed cancers, causing millions of deaths annually. Mouse model research suggests that myocardial infarction induces systemic changes, fostering cross-disease communication that expedites breast cancer. Using GEO2R for transcriptomic analysis, Cytoscape for protein-protein interaction (PPI), and EnrichR for enrichment analysis, we explored the myocardial infarction-breast cancer relationship with datasets from GEO. We identified 3,300 differentially expressed genes, including 6 commonly upregulated and 18 commonly downregulated genes. PPI and enrichment analyses revealed RAD51 genes associated with homologous recombination pathways (P-value 0.02032). Additionally, 4 genes (RAD51, KIF4A, DTL, and DLGAP5) were linked to CD105+ endothelial cells (P-value 0.00002216), connecting myocardial infarction and breast cancer. Nevertheless, further testing is needed for accurate results and to support this study's transcriptomic analysis.